2015
DOI: 10.1007/s11069-015-1835-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of social media in California’s drought risk management in 2014

Abstract: Social media creates an interactive information communication platform for disaster preparedness, mitigation, response, and recovery. Recent research has analyzed the participation of social media in natural disasters, such as the Haiti Earthquake in 2010, Queensland floods from 2010 to 2011, Hurricane Sandy in 2012, and Colorado flood in 2013, but little research has paid attention to drought risk management. In this study, the strengths, weaknesses, opportunities, and threats analysis method is used to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
91
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 16 publications
0
91
0
2
Order By: Relevance
“…Government agencies use their accounts to release information about updates and guidelines, but few employ participative strategies to promote citizen-government collaboration and engagement (Neely & Collins, 2018;Wukich, 2016). The two-way interactive communication through Government Social Media (GSM) stays on the surficial level, such as limited comments and inadequate dialogue (Tang, Zhang, Xu, & Vo, 2015). Secondly, government agencies may experience challenges in using social media for citizen engagement, including the digital divide, reliability and accountability, vague organizational strategies, lack of sufficient resources and formal policies, privacy, and security issues (Elbanna, Bunker, Levine, & Sleigh, 2019;Harrison & Johnson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Government agencies use their accounts to release information about updates and guidelines, but few employ participative strategies to promote citizen-government collaboration and engagement (Neely & Collins, 2018;Wukich, 2016). The two-way interactive communication through Government Social Media (GSM) stays on the surficial level, such as limited comments and inadequate dialogue (Tang, Zhang, Xu, & Vo, 2015). Secondly, government agencies may experience challenges in using social media for citizen engagement, including the digital divide, reliability and accountability, vague organizational strategies, lack of sufficient resources and formal policies, privacy, and security issues (Elbanna, Bunker, Levine, & Sleigh, 2019;Harrison & Johnson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Regan et al (2014) thematically explored dietary heath risk perceptions through online comments on two online media articles. Correspondingly, there is increased interest in studying online interactions across a range of water resource management domains, including through online participation tools (Bojovic, Bonzanigo, Giupponi, & Maziotis, 2015;White, Kingston, & Barker, 2010), social media (Tang, Zhang, & Xu, 2015) and online comments (Russell-Verma, Smith, & Jeffrey, 2015). A recent exploration of online comments on an aquifer recharge proposal (river water) in Finland concluded that debate on the subject was prone to polarization and lacked attention to benefits and risks (Lyytimaki & Assmuth, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The notifications from this system are delivered much faster than the announcements of the Japan Meteorological Agency, which are broadcast 6 min after an earthquake. Tang et al (2015) descriptively evaluated the strengths, weaknesses, opportunities, and threats of VGI in managing the California drought in 2014 and provided an overall description of the role of this system in disaster management. Apart from offering a practical tool for event detection, VGI provides a new level of interaction, participation, and engagement to citizens for environmental governance (Werts et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Internet-based applications allow people to conduct online communications intended for interaction, community input, and collaboration (Lindsay, 2011). Social media also allow multiple parties to share information using their computers or mobile devices, specifically through social networking sites (e.g., Facebook, YouTube, and Twitter), SMS, chatrooms, discussion forums, and blogs (Tang et al, 2015). Social media build on the ideological and technological foundations of Web 2.0, and enable the creation and exchange of user-generated content (Kaplan and Haenlein, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation